A Self‐Powered Wearable Sensor for Continuous Wireless Sweat Monitoring. Issue 10 (8th September 2022) - Gai, Yansong; Wang, Engui; Liu, Minghao; Xie, Lirong; Bai, Yuan; Yang, Yuan; Xue, Jiangtao; Qu, Xuecheng; Xi, Yuan; Li, Linlin; Luo, Dan; Li, Zhou
Abstract: Wireless wearable sweat analysis devices can monitor biomarkers at the molecular level continuously and in situ, which is highly desired for personalized health care. The miniaturization, integration, and wireless operation of sweat sensors improve the comfort and convenience while also bringing forward new challenges for power supply technology. Herein, a wireless self‐powered wearable sweat analysis system (SWSAS) is designed that effectively converts the mechanical energy of human motion into electricity through hybrid nanogenerator modules (HNGMs). The HNGM shows stable output characteristics at low frequency with a current of 15 mA and a voltage of 60 V. Through real‐time on‐body sweat analysis powered by HNGM, the SWSAS is demonstrated to selectively monitor biomarkers (Na + and K + ) in sweat and wirelessly transmit the sensing data to the user interface via Bluetooth. Abstract : A fully self‐powered wearable sweat analysis system is constructed, which harvests human kinetic energy via hybrid nanogenerators, performs selective in situ monitoring of biomarkers (Na + and K + ), and wirelessly transmits the sensing data to a user interface via Bluetooth. This work provides a promising strategy for advancing self‐powered wearable electronics and multifunctional health monitoring platforms.